Linkage mapping of the blond locus in Nile tilapia (Oreochromis niloticus L.) and preliminary analysis of its effect on blotching in red Nile tilapia - Rajaee, Amy Halimah; Palaiokostas, Christos; Saini, Ved Prakash; McAndrew, Brendan J.; Penman, David J. (Elsevier, 2014)
Black blotching of the skin in red tilapia is undesired by tilapia producers since it affects their marketability. This study was carried out with the aims of mapping the blond locus and testing whether the homozygous recessive blond gene reduces or removes blotching in red tilapia by studying the interaction between the red and blond genes. Two types of mapping families (two intraspecific and one interspecific) were used for the mapping of the blond locus. Genome-wide mapping using microsatellites was first carried out to identify molecular markers that were linked to the blond locus. The locus was mapped in linkage group (LG) 5 in an interval that varied between 7.5 and 20.8 cM, depending on the tested family. In the intraspecific families the blond locus was closely linked to the microsatellites UNH309, UNH169 and GM017 (P < 10− 11), while in the interspecific family microsatellite GM636 (P < 10− 8) was also found to be significantly associated, in addition to the above three microsatellites. Linked markers were used to identify the genotype of individual fish for the blond and red loci from the specifically designed crosses so the effect of recessive blond gene on blotched fish could be assessed. The underlying blond trait did not significantly reduce the area of blotching but did reduce the saturation (paler blotching) and enhanced the redness of body colour in the homozygous blond fish compared to the heterozygous (wild type) group.